The extent to which the university district teachers in Jordan practice multiple intelligences in the classroom and its relationship to some variables - Al- Khawaldeh, Hamzah Ali Abdullah (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the extent to which the university district teachers in Jordan practice multiple intelligences in the classroom and its relationship to some variables. To achieve the objectives of the study, a scale of (36) items was developed distributed on (8) intelligences from the theory of multiple intelligences, namely (linguistic intelligence, logical intelligence, spatial intelligence, physical intelligence, musical intelligence, social intelligence, and personal intelligence. The study sample consisted of (200) male and female teachers from government schools in the University Brigade Directorate, and the results of the study revealed the following:The study sample consisted of (200) male and female teachers of government schools in the Directorate of the University Brigade, and the study revealed that the degree to which teachers of the University Brigade in Jordan practice multiple intelligences in the classroom came with high degrees, as follows: logical intelligence, social intelligence, personal intelligence, linguistic intelligence and physical intelligence And spatial intelligence, with the exception of musical intelligence, which got an average degree. As well as the absence of statistically significant differences due to the effect of the gender of the teacher in all fields and in the total degree except for linguistic intelligence, and the differences came in favor of females. In addition to the absence of statistically significant differences due to the effect of academic qualification in all fields and in the total degree except for personal intelligence, and the differences came in favor of the bachelor's degree. The study recommended that attention should be given to holding courses on the theory of multiple intelligences to familiarize teachers with the importance of practicing them in the classroom.
Keywords: The theory of multiple intelligences; linguistic intelligence; logical intelligence; spatial intelligence; and musical intelligence